The Significance of Analyzing Different Levels in Identifying Spelling Mistakes Within News Articles - Wulan Apriliani; Bagus hari nugroho; Putri Puspita Sari (International Forum of Researchers and Lecturers, 2024)
This study investigates the impact of various levels of analysis on the detection and understanding of spelling errors in news texts. By employing different analytical approaches, including linguistic, contextual, and syntactic levels, this research aims to elucidate the nuances of spelling errors and their implications for news comprehension and credibility. The findings contribute to a deeper understanding of how different levels of analysis influence the identification and interpretation of spelling errors in news content, thereby informing strategies for enhancing text quality and reader engagement